The Effect of Giving Rewards and Punishment To Students' Interest In Learning In Mathematics Subjects Class IV Muhammadiyah 31 Medan Elementary School - Putri Azzizah Panjaitan; Marah Doly Nasution (Universitas Pendidikan Indonesia (UPI), 2024)
One aspect that plays an important role in life is education, especially in learning mathematics, where students first avoid it and think that mathematics is difficult, so this makes students' interest in learning decrease. The aim of this research is to find out the influence of giving rewards and punishment on students' interest in learning in mathematics subjects. The research method used in this research uses a quantitative approach with the instrument used, namely SPSS 25 for Windows, while the data collection technique uses a questionnaire and data analysis uses the classic assumption test. The research results show that 1) Rewards and punishments simultaneously influence students' interest in learning by 92 percent; 2) Compensation influences interest rates significantly, as shown by the sign value of 0.003 being less than 0.05; and 3) Compensation significantly influences students' interest in learning, as shown by the mark value of 0.002 which is less than 0.05. The punishment variable is the most influential in terms of its significance value. It can be concluded that the rewards and punishments given by teachers or educators to students influence their interest in learning mathematics subjects.